El texto argumentativo como estrategia mediada por las TIC para el fortalecimiento de la lectura crítica (2015)
The present research is intended to foster critical reading competencies using Communication and Information Technologies (CIT) by means of use of mediation and argumentative text to students attending first semester of Social Communication at Universidad de la Costa. This research has been leaded as a result of low level of critical reading detected on beginner students attending professional careers. This situation becomes visible and weaker as students advance their careers. As critical reading is an issue of great impact should be considered as a priority on cognitive development process of students. Therefore these initiatives to foster, stimulate, and improve the critical reading on students through a CIT strategy designed to foster and improve a high critical reading level required by new professional to face and comply on labour market. The present research was put into practice by means of a diagnostic test, also known as a pre-test to evaluate the level of reading of Social Communication students. Using CIT as a motivating strategy on students, these didactic sequences are screened though a validation process to make required adjustments. Then, starting from these didactic sequences the changes observed on interpretative processes of students should be described on.